2020
DOI: 10.2139/ssrn.3508589
|View full text |Cite
|
Sign up to set email alerts
|

Does China's Overseas Lending Favor the One Belt One Road Countries?

Abstract: The One Belt One Road initiative is found to promote China's overseas lending in the belt road countries, especially for countries along the continental route. Such effect strengthens and persists for at least three years. Our findings show that launching a national strategy could be a decisive determinant of one country's outbound loans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
2
4
0
1
Order By: Relevance
“…In addition, the results indicate that the nature and extent of the initial government response significantly affects the rate of spread, level of infection and mortality of Covid-19. These results extend those of Fang et al [2], Zhang et al [7] and Zimmermann et al [6] who analyzed the factors that explain the spread of the new coronavirus.…”
Section: Conclusion Remarks and Implicationssupporting
confidence: 90%
See 3 more Smart Citations
“…In addition, the results indicate that the nature and extent of the initial government response significantly affects the rate of spread, level of infection and mortality of Covid-19. These results extend those of Fang et al [2], Zhang et al [7] and Zimmermann et al [6] who analyzed the factors that explain the spread of the new coronavirus.…”
Section: Conclusion Remarks and Implicationssupporting
confidence: 90%
“…In addition, we show that the nature and level of rigour of the initial government measures explain the speed of spread, the level of infection and the mortality rate of the virus. Our results extend those of Zhang et al [7] and Fang et al [2] who have worked on the factors that explain the spread of Covid-19, without explicitly examining the consequences of government reactivity on the spread of this virus.…”
Section: Introductionsupporting
confidence: 87%
See 2 more Smart Citations
“…Much of the infrastructure has been financed by the Chinese policy and commercial banks and a significant share of Chinese loans in recent years has gone to BRI countries. One empirical study has found that countries that sign up for the BRI have received significantly more loans from China than those that have not (Zhang and Fang, 2020). The other side of increased loans is the growing indebtedness of the countries involved, giving rise to concerns over debt sustainability for a number of countries (Bandiera and Tsiropoulos, 2020; Hurley et al, 2018).…”
Section: China's Brimentioning
confidence: 99%